2022
DOI: 10.54117/gjpas.v1i2.37
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of raptor species relative abundance in Hadejia Nguru Wetlands, Nigeria

Abstract: Birds of prey are some of the most threatened vertebrate taxa, and in the last three decades many species have experienced severe population declines or faced extinction. The global loss of raptors per se is worrying, not just because of their charisma and flagship role, but also because reduced abundance of raptors can have cascading effects on ecosystem functioning. Raptor decline may also lead to loss of ecosystem services, sometimes acutely impacting human well-being. Therefore, population distribution, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
2
2
1
Order By: Relevance
“…Accipitridae with 24 species is the richest family in species number and Falconidae with 7 species. This result is in conformity with the findings of Sabo and Mohammed (2022) and Okosodo et al, (2016) who reported accipitridae as the richest family in their studies conducted at Hadejia-Nguru wetlands and South Western Nigeria respectively. It is also in agreement with Kabir (2013) who conducted his research in Bangladash and reported accipitradae as the richest family.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Accipitridae with 24 species is the richest family in species number and Falconidae with 7 species. This result is in conformity with the findings of Sabo and Mohammed (2022) and Okosodo et al, (2016) who reported accipitridae as the richest family in their studies conducted at Hadejia-Nguru wetlands and South Western Nigeria respectively. It is also in agreement with Kabir (2013) who conducted his research in Bangladash and reported accipitradae as the richest family.…”
Section: Resultssupporting
confidence: 92%
“…A similar result with species of Endangered, vulnerable category, Near Threatened and Least Concerned species has been previously reported from Hadejia-Nguru wetlands, Nigeria (Sabo and Mohammed, 2022). A variety of threats like sporadic fire, cattle grazing, mining and illegal Non Timber Forest Product collection by local communities affecting the safe nesting, roosting sites and prey base and eventually the population size.…”
Section: Resultssupporting
confidence: 84%
“…Columbidae might be as a result of rice farming that is predominant in the area. The result is in contrast with the findings ofSabo (2016) who conducted a study in the same ecological area of Hadejia-Nguru wetlands and observed that only 135 species against the 50 species were identified along the RB. Similarly,Odewumi et al, (2017), reported that there were fewer number of 35 bird species belonging to 20 families were identified and recorded, the common species identified in includes Great egret (Ardea alba), Spur winged lapwing (Vanellus spinosus), Black Kite (Milvus migrans), Cattle egret (Bubulcus ibis) in Owena Multipurpose Dam, Ondo State, Southwest, Nigeria.…”
contrasting
confidence: 99%
“…In Nigeria, four (4) avifauna species; Anambra waxbill (Estrilda poliopareia), Ibadan Malimbe, (Malimbus ibadanensis), Jos Plateau indigo-bird (Vidua maryae) and the Rock Fire-Finch (Lagonosticta sanguinodorsalis) are endemic to the country, making them globally important species for conservation (Nigeria National Biodiversity strategy and action plan NBSAP, 2007). Previous studies on the avifauna resources were carried out at Dagona Waterfowl Sanctuary by Lameed, 2011; Hadejia-Nguru Wetlands by Ringim and Sulaiman, 2017;Sabo, 2016. All these studies covered the Dagona-Nguru-Hadejia wetland which is congruent with river Yobe.…”
Section: Introductionmentioning
confidence: 99%
“…Observations were made in the morning from 06.00-09.00 and afternoon from 15.00-18.00 (Asrianny et al 2018;Lwin 2018;Iswandaru et al 2020a;Ramadhani et al 2022). Observers strolled along the transect, and each encounter recorded the type of bird observed (Sabo et al 2022). In addition, bird species are recorded at each direct encounter.…”
Section: Methodsmentioning
confidence: 99%